ANTI PENGKULTUSAN SEBAGAI KARAKTERISTIK PENDIDIK IDEAL DAN RELEVANSINYA DI ERA MODERN: TELAAH ASBᾹB AL-NUZŪL SURAH ᾹLI ‘IMRᾹN (3): 79 - Eka Sulistiyawati; Thobroni, Ahmad Yusam; Annisa, Anni (Al - Tadabbur: Jurnal Ilmu Al-Qur'an dan Tafsir, 2024)
This study aims to examine anti-idolization as a characteristic of the ideal educator, based on the asbāb al-nuzūl (circumstances of revelation) of Qs. Ᾱli ‘Imrān (3): 79. This verse provides a warning to the Jewish and Christian communities during the time of Prophet Muhammad SAW, who tended to idolize their religious figures. This study employs a descriptive-qualitative method with a library research approach. Data sources are drawn from classical tafsir (exegesis) and relevant literature on Islamic educational concepts. The analysis is conducted by interpreting the verse within its socio-historical context and linking it to modern educational conditions. The findings indicate that the principle of anti-idolization is highly relevant in the modern era, where excessive dependence on educators or authority figures can hinder students' freedom of thought and intellectual independence.